Financial Literacy, Job Satisfaction, Job Performance And Organizational Performance: New Evidence - Wazdi, Babay Parid; Yuliawati, Ayu Krishna; Rofaida, Rofi; Sari, Maya (UNIVERSITAS PAKUAN, 2020)
This study aims to re-examine: (1) the effect of financial literacy on job performance. (2) The effect of job satisfaction on job performance. (3) The effect of job satisfaction on organizational performance. (4) The effect of job performance on organizational performance and; (5) The effect of job satisfaction on organizational performance through job performance. We took Bank North Sumatera (Bank Sumut) as the locus study which is one of the Regional Development Banks in Indonesia. This study used Mixed Method Research for analyzing and combining quantitative and qualitative approaches with a sequential explanatory design and will be carried out in 2 stages. At the quantitative analysis stage, we used a path analysis approach which divided into 2 structural models. At this stage we used a questionnaire for collecting data with a total of 1,370 respondents. Furthermore, at the qualitative analysis stage, we carried out a verification analysis to confirm the findings obtained from the quantitative analysis. At this stage we interviewed 3 top executives of Bank Sumut, as follows the Director, Strategy and Transformation Division Leader, and Funds and Services Division Leader to answer the research problems. This study has the conclusions: (1) financial literacy has a positive and significant effect on job performance (2) job satisfaction has a positive and significant effect on organizational performance. These results indicate that these two variables are important variables for improving job/organizational performance.